Vocational Education - Billett, Stephen. author. (orcid)0000-0002-9926-3518 Link aut Link
XV, 266 p.
Keywords: This book discusses what constitutes vocational education as well as its key purposes, objects, formation and practices. In short, it seeks to outline and elaborate the nature of the project of vocational education. It addresses a significant gap in the available literature by providing a single text that elaborates the scope and diversity of the sector, its key objectives (i.e. vocations and occupations), its formation and development as an education sector, and the scope of its purposes and considerations in the curriculum. The volume achieves these objectives by discussing and defining the concept of vocational education as being that form of education that seeks to advise individuals about, prepare them for, and further develop their capacities to perform the kinds of occupations that societies require and individuals need to participate in—and through which they often come to define themselves. In particular, it discusses the distinctions between occupations as a largely social fact and vocations as being a socially shaped outcome assented to by individuals. As people identify closely with the kinds of occupations they engage in, the standing of, and the effectiveness of vocational education is central to individuals’ well-being, competence and progress. Ultimately, this book argues that the provision of vocational education needs to realise important personal and social goals.